Impact of Cylinder Deactivation and Cylinder Cutout via Flexible Valve Actuation on Fuel Efficient Aftertreatment Thermal Management at Curb Idle - Vos, Kalen R.; Shaver, Gregory M.; Ramesh, Aswin K.; McCarthy, James (Frontiers in Mechanical Engineering, 2019)
Cylinder deactivation (CDA) and cylinder cutout are different operating strategies for diesel engines. CDA includes the deactivation of both the valve motions and the fuel injection of select cylinders, while cylinder cutout incorporates only fuel injection deactivation in select cylinders. This study compares diesel engine aftertreatment thermal management improvements possible via CDA and cylinder cutout at curb idle operation (800 RPM and 1.3 bar BMEP). Experiments and analysis demonstrated that both CDA and cylinder cutout enable improved fuel efficient “stay warm” thermal management compared to a stock thermal calibration on a Clean Idle Certified engine. At curb idle, this stock calibration depends on elevated exhaust manifold pressure to increase the required fueling (for thermal management) and to drive EGR. The study described here demonstrates that CDA does not require an elevated exhaust manifold pressure for thermal management or EGR delivery control, whereas cylinder cutout does. In addition to achieving engine-out NOx levels no higher than the stock thermal calibration, both cylinder cutout and CDA enable up to 55% and 80% reductions in particulate matter (PM), respectively. Cylinder cutout demonstrates 17% fuel savings, while CDA demonstrates 40% fuel savings, over the stock six-cylinder thermal calibration. These fuel efficiency improvements primarily result from reductions in pumping work via reduced air flow through the engine. Cylinder cutout reduces the air flow rate via elevated amounts of recirculated gases which are also required to regulate engine-out NOx, resulting in a larger delta pressure across the engine and consequently more pumping work than CDA. CDA reduces the air flow rate by deactivating cylinders, which reduces the charge flow rate and enables a small delta pressure between the intake and exhaust manifolds, resulting in less pumping work by the cylinders. As a result, CDA is more efficient than cylinder cutout. Furthermore, the thermal merits of cylinder cutout require high exhaust manifold pressures, and are subject to the configuration of the exhaust manifold and the exhaust gas recirculation (EGR) path.